HEMODYNAMIC ANALYSIS OF BLOOD VESSELS BASED ON COMPUTATIONAL FLUID DYNAMICS WITH DIFFERENT SOFTWARE - Zaki Rahmani, Farhan
An aneurysm is an abnormal condition characterized by the swelling of a blood vessel, if left untreated, can lead to the vessel rupturing. One effective therapy to minimize the impact of an aneurysm is the placement of a flow-diverting stent (PA), which aims to reduce the blood flow entering the aneurysmal area. Currently, the method of in silico PA stent placement, known as virtual stenting (VS) is employed. In practice, VS is performed using the Fast Virtual Stenting (FVS) method to simulate FD stent placement, followed by evaluating its effectiveness through Computational Fluid Dynamics (CFD) simulations, all of which are conducted using open-source software. Open-source software has several advantages, such as the absence of licensing fees and flexibility in algorithm modification. However, challenges remain due to the lack of standardized protocols in open-source software. Therefore, it is necessary to systematically verify the implementation of FVS and CFD methods on open-source software and validate the simulation results by comparing them with those from licensed software.